Dual study programmes as a design challenge : identifying areas for improvement as a starting point for interventions - Mordhorst, Lisa [Verfasser]; Gössling, Bernd [Verfasser] (My University, 2020)
"The proportion of freshmen enrolled in dual study programmes has steadily increased in recent years. From the perspective of potential students, these programmes are highly attractive because they combine types of learning that used to be largely separate at an institutional level: vocational and academic learning. In training-integrated dual study programmes, different institutional contexts, governance regimes, teaching styles and learning environments make bridging these two worlds of learning a challenge for both educators and learners. However, these programmes also allow leeway for didactic innovation, through the cooperation of different types of educational institutions and through new ways of using available didactic methods, and for establishing a new relationship between higher education (HE) and vocational education and training (VET). This paper positions training-integrated dual study programmes as an object of design-based research (DBR). By developing and using an extended model for the pedagogic development of HEIs, “pädagogische Hochschulentwicklung” (Brahm, Jenert, & Euler, 2016a, p. 19; Euler, 2013, p. 360), the paper systematically identifies generic educational problems in these hybrids. Based on a literature review, this paper classifies and explains the design challenges at the level of the learning environment, the study programme and the organisation. The challenges revolve mainly around the cooperation and integration of HE and VET. The paper concludes with an outlook on future DBR projects designing dual studies." (Authors' abstract, BIBB-Doku)
Keywords: T 1 Forschungsrichtungen; T 3 Forschungsmethoden; S 1.4 Hochschulbildung; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; L 2.2 Didaktik; Berufsbildungsforschung; Gestaltungsbasierte Forschung; Dualer Studiengang; Durchlässigkeit im Bildungssystem; Hochschuldidaktik; Lernumgebung